Opportunistic discovery of information by elderly Icelanders and their relatives - Ágústa Pálsdóttir 1955- (2011)
Introduction. This paper discusses an exploratory study of the opportunistic discovery of information by elderly people in Iceland who are still living in their own homes as well as by their relatives who act as care providers and support their information behaviour. Method. Open-ended interviews were conducted with twenty-four people, twelve of whom were aged 70 to 90 and twelve of whom were their relatives. Analysis. Analysis of the data was conducted according to grounded theory as described by Strauss and Corbin and the themes that emerged interpreted in terms of the context relating to each participant. Results. The information that the elderly people discovered reflect their everyday life problems and concerns. Information about formal support, health information and information about finances were most often mentioned. Their relatives discovered information about health and formal support. The information were discovered in the media and through discussions with family members, friends and acquaintances. Two information grounds supported the elderly participants’ opportunistic discovery of information: an association for the elderly and a sewing club. Conclusions. The findings suggest that opportunistic discovery of information and information sharing with others forms a significant part of the elderly participants’ information behaviour. Although their relatives also discovered information, this happened less often and was confined to fewer topics.